Technoprener di Politeknik Negeri Bengkalis: Technoprener di Politeknik Negeri Bengkalis - Suharyono Suharyono (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The Entrepreneurship Development Program aims to implement entrepreneurial practices and civilize entrepreneurship for Bengkalis State Polytechnic students and graduates that are in line with the field of academic science in order to realize technopreneur. The target of this activity every year is to produce five or more technopreneurs who have the mental and entrepreneurial character that is intelligent, strong determination, discipline, hard-working, confident, risk taker, never give up, honest, creative, innovative, and sincere. To realize this target, the team has conducted an information dissemination on the Entrepreneurship Development Program to students and graduates. Then proceed with the selective recruitment of tenant participants. Tenant participants who pass the selection will get entrepreneurship training. In addition, participants will also take part in internships in businesses that are in accordance with their business ideas or conduct benchmarking visits. During the Entrepreneurship Development Program activities, the team will provide guidance, assistance and or consultancy to tenants to be able to produce prospective, innovative and economical academic-based businesses.